VISTA is associated with immune infiltration and predicts favorable prognosis in TNBC - Zhang, Mi; Zhang, Juan; Liu, Na; Wang, Biyuan; Zhou, Yan; Yang, Jin (Frontiers in Oncology, 2022)
Background: V-domain Ig-containing suppressor of T cell activation (VISTA), a critical immune checkpoint protein, can regulate the immune system. Nevertheless, little information is available on the expression level of VISTA and its clinical significance as well. The immunological and prognostic role of VISTA in triple-negative breast cancer (TNBC) still remains unclear. Methods: The clinical significance and expression of VISTA in TNBC were examined using RNA sequencing and clinical data. Prognostic analysis was performed using Kaplan-Meier plotter. Moreover, cancer single-cell state atlas (CancerSEA) was utilized to assess the function at single-cell level. Furthermore, the correlation between VISTA and tumor immune infiltration was explored using gene set enrichment analysis (GSEA), single sample GSEA, and ESTIMATE algorithm. In the end, our findings were verified by the immunohistochemical staining. Results: VISTA was down-regulated (P = 0.0004) and closely associated with good prognosis (P = 0.0033) in TNBC. The expression of VISTA was higher in younger TNBC patients (≦60 years), Immunity-H group and immunomodulatory (IM) subtype. The level of VISTA expression in TNBC gradually increased with the degree of stromal tumor infiltrating lymphocytes (sTILs) infiltration. In addition, the high expression of VISTA was strongly linked to higher proportion of CD8 (+) T cell and M1 macrophages. Conclusion: VISTA was remarkably correlated with a favorable prognosis and high immune infiltration in patients with TNBC.